Examining Factors that Influence Harumanis Farmers’ Intention to Use Safe Pesticides (Global Business Management Review (GBMR), 2021)
Harumanis demands delicate handling and farmers must know how to use safe pesticides. Therefore, the aim of this study is to examine factors influencing the use of safe pesticide among Harumanis farmers in Mata Ayer, Perlis. The Theory of Planned Behavior (TPB) was used to underpin this study. This study suggests that attitude, subjective norm, perceived behavioral control, knowledge and moral norm as the variables that influence the use of safe pesticides. Data were collected from 97 registered Harumanis farmers under Department of Agriculture (DOA) Malaysia through questionnaires. SmartPLS was used to test the hypotheses in this study. The results showed that attitude, moral norm and knowledge had positive effects on the intention to use safe pesticides. Moreover, subjective norm and perceived behavioral control exhibited insignificant effect on the dependent variable. The results provide helpful information to the stakeholders in the Harumanis industry, from which they could develop and improve appropriate strategies and provide essential assistance to the Harumanis farmers.